Effect of Variations in Banana Frond Fiber Composition with Polyurethane Matrix on Composite Panels Acoustic Properties and Porosity - Oktavia, Vini; Darvina, Yenni; Ramli, Ramli; Hidayat, Rahmat (Journal of Experimental and Applied Physics, 2023)
Noise can damage one's health, affect one's comfort, cause stress, and make activities not run smoothly. Making acoustic materials is one of the efforts made to overcome noise pollution. The material used in this study comes from banana fiber with a polyurethane matrix. This research material is easily and widely available. The advantage of this study is to determine the effect of variations in the composition of banana stem fiber with a polyurethane matrix on the values of the sound reflection coefficient, sound absorption coefficient, sound transmission loss, and porosity. The method used is a hand lay-up with a single microphone tube impedance characterization tool and an analytical balance. In this study, variations in the composition of the composite panels with fiber and matrix variations were carried out, namely 60%:40%, 70%:30%, and 80%:20%. Based on the findings of this study, the higher the sound absorption coefficient, sound transmission loss, and porosity, the lower the sound reflection coefficient. If the frequency used is higher, the values of the sound absorption coefficient and transmission loss increase, while the reflection coefficient decreases for the entire frequency range. If the porosity is higher, the acoustic properties will be better, which is indicated by an increase in the value of the sound absorption coefficient and the value of the sound transmission loss. High porosity will comply with the ISO 11654:1997 standard.